What does community resilience mean in the context of trauma‐informed communities? A scoping review. Issue 8 (23rd March 2022) - King, Lindsey M.; Zori, Gaia; Collins, Sarah L.; Lewis, Carol; Hack, George; Dixon, Brittney N.; Hart, Mark
Abstract: Several communities are implementing trauma‐informed, community‐level approaches focused on addressing/preventing adverse childhood experiences (ACEs), yet most community resilience definitions from published articles are based on acute traumas. This scoping review aims to determine how community resilience is defined and operationalized within the context of chronic/complex traumas. Methods: We performed a rigorous, comprehensive literature search using multiple databases. Results: The 38 included articles addressed multiple types of chronic traumas, including historical trauma, poverty, minority stress, mass incarceration, and ACEs. A variety of definitions of community resilience were cited, several of which stressed the ability to thrive despite risk factors and the safety and wellbeing of residents. Few articles operationalized community resilience within the context of ACEs, suggesting significant gaps in the literature. Conclusion: This review can serve as an important building block to develop expanded definitions of community resilience for chronic traumas and assist communities in promoting community‐wide responses to ACEs.